Do newly founded firms pay lower wages? First evidence from Germany - Udo Brixy; Susanne Kohaut; Claus Schnabel (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2004)
Using a linked employer-employee data set for Germany, this paper analyses wage setting in a cohort of newly founded and other establishments from 1997 to 2001. While theory provides alternative explanations for higher or lower wages in newly founded firms, we show empirically that start-ups tend to pay lower wages, ceteris paribus. On average, wages in newly founded establishments are 8 percent lower than in similar incumbent firms. This negative wage differential is substantially smaller in eastern than in western Germany. The wage differential is shown to decline over time as the newly founded firms become more mature.
Keywords: D21; J30; 330; IAB-Linked-Employer-Employee-Datensatz; Unternehmensgründung; Unternehmensalter; Lohnstruktur; Lohnhöhe; Unternehmensgründung; Lohn; Lohnstruktur; Unternehmensentwicklung; Schätzung; Deutschland